Camulodunum: first report on the excavations at Colchester, 1930-1939 - Hawkes, C.F.C (Reports of the Research Committee of the Society of Antiquaries of London, 1947)
This work describes excavations in Colchester, England, carried out in 1930-9. Colchester was the site of the pre-Roman oppidum of Camulodunon and later town of Colonia Claudia Victricensis. This first report records the exploration of its principal inhabited centre, the area known as Sheepen. The description of the work is introduced by a topographical and historical account of Camulodunum, an exposition of the chronology of the Sheepen site, and a synopsis of the results in general. It is followed by a systematic presentation of the finds-coins, pottery, glass, metalwork, and animal and vegetable remains.